Paraendodontic surgery associate with photodynamic therapy: case report with 4 years follow-up (Research, Society and Development, 2021)
Parendodontic surgery is a set of procedures that aim to repair complications that could not be solved by conventional endodontics, or when it is not amenable to execution. This study aimed to describe the clinical case of a parendodontic surgery associated with photodynamic therapy on the upper right central incisor. The case was conducted with access to the root canal system in a retrograde way. Were performed: intra/extra buccal antisepsis, infiltrative anesthesia, surgical flap for access, the surgical cavity, apicectomy, retroinstrumentation, photodynamic therapy, retrofilling, filling the surgical cavity, flap repositioning, suture and a 4-year cone beam follow-up. We conclude that the association of the surgical procedure with the application of low-level laser through photodynamic therapy has enhanced the disinfection and elimination of persistent bacteria to the failure of the previous endodontic treatment, providing additional benefits to the patient when compared to conventional surgical techniques.